Chapter Advanced Microfluidic Assays for Caenorhabditis elegans - Bakhtina, Natalia A. (InTechOpen, 2016)
Gait function can be altered after incomplete spinal cord (iSCI) lesions. Muscular weakness, co‐activation of antagonist muscles, and altered muscle mechanics are likely to provoke abnormal gait and postural movements. Functional scales are available for assessment of functional walking in SCI patients, such as walking index for spinal cord injury (WISCI II), timed up and go (TUG) test, 10‐meter walk test (10MWT), and 6‐minute walk test (6MWT). Novel metrics for a more detailed comprehension of neuromuscular control in terms of degree of voluntary motor control have been recently proposed. This section describes novel techniques based on muscle synergy and frequency domain analysis of electromyographic signals. Such techniques are illustrated as potential tools for assessment of motor function after SCI with experimental data and a case study describing a diagnostic scenario. This chapter presents a discussion of the current status of the emerging metrics for assessment of sensorimotor impairments. Conclusions are given with respect to the availability of enriched information about neuromuscular behavior between functional tasks (walking and pedalling) and the potential relevance of these new techniques to improve the efficacy of treatment to improve locomotion after iSCI.